Proceedings of the 2016 International Conference on Advanced Electronic Science and Technology (AEST 2016) 2016
DOI: 10.2991/aest-16.2016.111
|View full text |Cite
|
Sign up to set email alerts
|

Development of g10kv 4H-SiC SBD junction extension termination

Abstract: 10kV 4H-SiC JBS diodes with various junction extension terminations have been experimentally realized. The protection efficiencies of single JTE and modulation JTE terminations were investigated by means of numerical simulations. The JTE dose window to achieve the high protection efficiency has been enlarged, which indicates the robustness to the deviation of effective JTE dose and SiO2/SiC interface charge. The samples with the single JTE, two-zone JTE, three-zone JTE and improved three-zone JTE terminations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The results showed that, for 90% of the theoretical BV, a conventional SZ-JTE obtained a narrow JTE dose tolerance of 1.0 × 10 12 cm −2 . Therefore, many modified forms of JTE have been proposed to improve the sensitivity, such as guard ring-assisted JTE (GA-JTE) [15,16,17], double-zone JTE (DZ-JTE) [18,19], multiple-zone JTE (MZ-JTE) [20,21], etched JTE [22,23], counter-doped JTE (CD-JTE) [24], and mesa combined with JTEs [25,26]. Feng [14] also reported that the JTE dose tolerance (4.8 × 10 12 cm −2 ) in the conventional DZ-JTE was improved compared with the conventional SZ-JTE.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that, for 90% of the theoretical BV, a conventional SZ-JTE obtained a narrow JTE dose tolerance of 1.0 × 10 12 cm −2 . Therefore, many modified forms of JTE have been proposed to improve the sensitivity, such as guard ring-assisted JTE (GA-JTE) [15,16,17], double-zone JTE (DZ-JTE) [18,19], multiple-zone JTE (MZ-JTE) [20,21], etched JTE [22,23], counter-doped JTE (CD-JTE) [24], and mesa combined with JTEs [25,26]. Feng [14] also reported that the JTE dose tolerance (4.8 × 10 12 cm −2 ) in the conventional DZ-JTE was improved compared with the conventional SZ-JTE.…”
Section: Introductionmentioning
confidence: 99%